2016
DOI: 10.21109/kesmas.v11i2.801
|View full text |Cite
|
Sign up to set email alerts
|

Family Planning Information, Education and Communication with Contaceptive Use

Abstract: Contraceptive use prevalence in Indonesia within the last decade (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) did not significantly increase, although many Family Planning Information, Education and Communication activities had been performed. This study aimed to determine socioeconomic demographic factors related to Family Planning Information, Education, Communication, any Information, Education and Communication elements related to contraceptive use and Information, Education and Commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 8 publications
0
14
0
1
Order By: Relevance
“…The education provided plays an important role in influencing a mother to decide the appropriate contraception method. 27 These educational efforts require ini-tial information on the individuals' understanding of the knowledge shared. However, few studies have been conducted to determine the correlation between the knowledge and behavior of breastfeeding mothers towards the application of LAM.…”
Section: Introductionmentioning
confidence: 99%
“…The education provided plays an important role in influencing a mother to decide the appropriate contraception method. 27 These educational efforts require ini-tial information on the individuals' understanding of the knowledge shared. However, few studies have been conducted to determine the correlation between the knowledge and behavior of breastfeeding mothers towards the application of LAM.…”
Section: Introductionmentioning
confidence: 99%
“…IEC materials were useful tools for promoting suitable eye awareness and also powers for social change in Madurai, India [ 33 ]. Similarly, it was observed that IEC and contraceptive uses were significantly associated beyond the visits of medical and family planning officers which was experienced in Indonesia [ 34 ]. A study from Gambia shows that mass media was an effective and feasible means to make a change in maternal health service utilization and care [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…IEC materials were useful tool for promoting suitable eye awareness and also a powerful for social change in Madhurai, India (29). Similarly, it was observed that IEC and contraceptive uses were significantly associated beyond the visits of medical and family planning officers which was experienced in Indonesia (30). A study from Gambia shows that mass media was effective and feasible means to make change in maternal health service utilization and care (31).…”
Section: Characteristics Of Respondents and Householdsmentioning
confidence: 99%